REVIEW OF RESEARCH ON DIVIDEND POLICY AND THE REFINANCING - Baoxin Tian Jianqiong Wang (International Journal of Research Science and Management, 2016)
Dividend policy and refinancing are both significant for the operation and development of all the listed company. In recent years, there are more and more studies on the refinancing and dividend distribution of listing Corporation. Research findings of refinance, dividend distribution, and refinancing and dividend distribution were reviewed in this paper.